A Novel Microbial Culture Chamber Co-cultivation System to Study Algal-Bacteria Interactions Using Emiliania huxleyi and Phaeobacter inhibens as Model Organisms - Thøgersen, Mariane S.; Melchiorsen, Jette; Ingham, Colin; Gram, Lone (Frontiers in Microbiology, 2018)
Our understanding of microbial natural environments combines in situ experimentation with studies of specific interactions in laboratory-based setups. The purpose of this work was to develop, build and demonstrate the use of a microbial culture chamber enabling both in situ and laboratory-based studies. The design uses an enclosed chamber surrounded by two porous membranes that enables the comparison of growth of two separate microbial populations but allowing free exchange of small molecules. Initially, we tested if the presence of the macroalga Fucus vesiculosus inside the chamber affected colonisation of the outer membranes by marine bacteria. The alga did indeed enrich the total population of colonizing bacteria by more than a factor of four. These findings lead us to investigate the effect of the presence of the coccolithophoric alga Emiliania huxleyi on attachment and biofilm formation of the marine bacterium Phaeobacter inhibens DSM17395. These organisms co-exist in the marine environment and have a well-characterised interdependence on secondary metabolites. P. inhibens attached in significantly higher numbers when having access to E. huxleyi as compared to when exposed to sterile media. The experiment was carried out using a wild type (wt) strain as well as a TDA-deficient strain of P. inhibens. The ability of the bacterium to produce the antibacterial compound, tropodithietic acid (TDA) influenced its attachment since the P. inhibens DSM17395 wt strain attached in higher numbers to a surface within the first 48 hour of incubation with E. huxleyi as compared to aa TDA-negative mutant. Whilst the attachment of the bacterium to a surface was facilitated by presence of the alga, however, we cannot conclude if this was directly affected by the algae or whether biofilm formation was dependent on the production of TDA by P. inhibens, which has been implied by previous studies. In the light of these results, other applications of immersed culture chambers are suggested.